The Global Extent of the Grassland Biome and Implications for the Terrestrial Carbon Sink - MacDougall, AS; Vanzant, B; Sulik, J; Bagchi, S; Naidu, D; Muraina, TO; Seabloom, EW; Borer, ET; Wilfahrt, P; Slette, I; Hierro, JL; Pearson, DE; et al. (Nature Research, 2026)
Land cover data are commonly used to model the terrestrial carbon (C) sink, yet these data have wide margins of error that significantly alter estimates of global C storage. Here we demonstrate this data vulnerability in grasslands, which are critical to C cycling but whose estimated distribution has varied by >50 million km² (3.5-42% of the Earth's terrestrial surface). Comparing multiple high-resolution land cover products with expertly annotated grassland data from six continents, we show sources of mapping error and discuss C implications based on 2023 United Nations (UN) FAO estimates. Past misidentification arose from inconsistent definitions on grassland identity and classification flaws especially relating to woody plant cover. Correcting these errors adjusted grassland coverage to 22.8% of the terrestrial land base (30.1 million km²), elevating UN projections of soil C stocks to 155.02 Pg (0-30 cm depth). These findings underscore the challenges of biome mapping for ecosystem accounting and policy, when lacking field-validated remotely sensed data.
Keywords: 41 Environmental Sciences; 4104 Environmental Management; 15 Life on Land; 3103 Ecology; 3104 Evolutionary biology; 4104 Environmental management; Grassland; Carbon Sequestration; Ecosystem